2008
DOI: 10.1021/jp711335b
|View full text |Cite
|
Sign up to set email alerts
|

Annular Structures as Intermediates in Fibril Formation of Alzheimer Aβ17−42

Abstract: We report all-atom molecular dynamics simulations of annular β-amyloid (17-42) structures, singleand double-layered, in solution. We assess the structural stability and association force of Aβ annular oligomers associated through different interfaces, with a mutated sequence (M35A), and with the oxidation state (M35O). Simulation results show that single layered annular models display inherent structural instability: one is broken down into linear-like oligomers, and the other collapses. On the other hand, a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 54 publications
4
64
0
Order By: Relevance
“…There are no reports detailing the SEM appearance of amyloidoma. While microtubular morphology, apart from immunotactoids, has not been described in clinical cases of amyloidoma or amyloidosis examined ultrastructurally, the theoretical existence of an annular structure that may serve as an intermediary in the protein folding process leading to insoluble amyloid fibers had been postulated [10].…”
Section: Discussionmentioning
confidence: 99%
“…There are no reports detailing the SEM appearance of amyloidoma. While microtubular morphology, apart from immunotactoids, has not been described in clinical cases of amyloidoma or amyloidosis examined ultrastructurally, the theoretical existence of an annular structure that may serve as an intermediary in the protein folding process leading to insoluble amyloid fibers had been postulated [10].…”
Section: Discussionmentioning
confidence: 99%
“…MD simulations of the oligomerization process of amyloidogenic proteins are becoming increasingly relevant [44][45][46][47]. However, an explicit atomistic description of the solvation phenomena described in the present work remains computationally very expensive, due to the very large number of participating water molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, our previous MD simulations have reported two stable doublelayer A oligomers associated by the N-terminal-N-terminal interactions via Gln15-Ala21 contacts for A 9-40 48 and Lys16-Glu22 contacts for A . 49 Recently, Miller et al 50 further confirmed the existence of double-layer A 17-42 oligomer forming a N-terminal-N-terminal interface. Thus, it appears that the N-terminal-N-terminal association observed in different structural symmetries can also contribute to A fibril formation.…”
Section: Discussionmentioning
confidence: 95%